C4 photosynthetic machinery: insights from maize chloroplast proteomics - Zhao, Qi; Chen, Sixue; Dai, Shaojun (Frontiers in Plant Science, 2013)
C4 plants exhibit much higher CO2 assimilation rates than C3 plants. The specialized differentiation of mesophyll cell (M) and bundle sheath cell (BS) type chloroplasts is unique to C4 plants and improves photosynthesis efficiency. Maize (Zea mays) is an important crop and model with C4 photosynthetic machinery. Current high-throughput quantitative proteomics approaches (e.g., 2DE, iTRAQ, and shotgun proteomics) have been employed to investigate maize chloroplast structure and function. These proteomic studies have provided valuable information on C4 chloroplast protein components, photosynthesis, and other metabolic mechanisms underlying chloroplast biogenesis, stromal and membrane differentiation, as well as response to salinity, high/low temperature, and light stress. This review presents an overview of proteomics advances in maize chloroplast biology.